Branched Poly(ethylene imine)s as Anti-algal and Anti-cyanobacterial Agents with Selective Flocculation Behavior to Cyanobacteria over Algae - Mikula, Premysl; Mlnarikova, Marie; Takahashi, Haruko; Babica, Pavel; Kuroda, Kenichi; Blaha, Ludek; Sovadinova, Iva (Macromolecular bioscience, 2018)
Poly(ethylene imine)s (PEIs) have been widely studied for biomedical applications, including antimicrobial agents against potential human pathogens. The interactions of branched PEIs (B-PEIs) with environmentally relevant microorganisms whose uncontrolled growth in natural or engineered environments causes health, economic, and technical issues in many sectors of water management are studied. B-PEIs are shown to be potent antimicrobials effective in controlling the growth of environmentally relevant algae and cyanobacteria with dual-functionality and selectivity. Not only did they effectively inhibit growth of both algae and cyanobacteria, mostly without causing cell death (static activity), but they also selectively flocculated cyanobacteria over algae. Thus, unmodified B-PEIs provide a cost-effective and chemically facile framework for the further development of effective and selective antimicrobial agents useful for control of growth and separation of algae and cyanobacteria in natural or engineered environments.
Keywords: polyethyleny; antiinfekční látky; flokulace; iminy; Synechococcus; Chlamydomonas reinhardtii; Imines; Microcystis; Polyethylenes; Flocculation; Anti-Infective Agents